2021
DOI: 10.1002/ange.202016734
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Analysis of Isomeric Unsaturated Lipids through Online Photochemical Derivatization of Carbon–Carbon Double Bonds**

Abstract: Unraveling the complexity of the lipidome requires the development of novel approaches for the structural characterization of lipid species with isomer-level discrimination. Herein, we introduce an online photochemical approach for lipid isomer identification through selective derivatization of double bonds by reaction with singlet oxygen. Lipid hydroperoxide products are generated promptly after laser irradiation. Fragmentation of these species in a mass spectrometer produces diagnostic fragments revealing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…On the other hand, the combination of functional group specific derivatization and MS 2 CID greatly expands the capability of detailed structural analysis of lipids on commercial MS platforms. Notable methods include epoxidation (23,24), converting C=C to hydroperoxides via singlet oxygen (25), and the Paternò-Büchi (PB) reaction (26). The PB-MS/MS approach has been adopted by several groups and applied to common lipid analysis workflows, including shotgun (27), direct analysis (28), LC-MS (29), and MS-imaging (30).…”
mentioning
confidence: 99%
“…On the other hand, the combination of functional group specific derivatization and MS 2 CID greatly expands the capability of detailed structural analysis of lipids on commercial MS platforms. Notable methods include epoxidation (23,24), converting C=C to hydroperoxides via singlet oxygen (25), and the Paternò-Büchi (PB) reaction (26). The PB-MS/MS approach has been adopted by several groups and applied to common lipid analysis workflows, including shotgun (27), direct analysis (28), LC-MS (29), and MS-imaging (30).…”
mentioning
confidence: 99%
“…As shown in Fig. 2 e, MS image of lipid hydroperoxides (LOOH), indicated that PC 34:1(LOOH) was enhanced in the gray matter (case ii); however, MS 2 I indicated that more 9Δ isomer than the 11Δ isomer existed in the white matter (cases iii and iv) [ 54 ].
Fig.
…”
Section: Mass Spectrometry Imaging (Msi) Of Tissues Using Direct Samplingmentioning
confidence: 99%
“…However, the information regarding the C=C locations within the fatty acyl chains was hardly provided through CID MS/MS alone [11,12]. Thus, site-specific derivatization on C=C bonds, such as epoxidation [13][14][15][16], singlet oxygen ene reaction [17], and the Paternò-Büchi (PB) reaction [18,19], have been developed to enable double bond localization in conjunction with CID. Ultraviolet photodissociation (UVPD) as an alternative ion activation method has been utilized independently for providing detailed structural characterization of intact lipids [20][21][22].…”
Section: Introductionmentioning
confidence: 99%